Biologia, direitos humanos e educação: diálogos necessários - VIEIRA, Eduardo Paiva de Pontes (Universidade Federal do Pará, 2011)
In this research I investigate in the modern biological speech, theories and propositions that legitimate the social equalities and differences through arguments considered scientific, in order to establish a relation with the Human Rights Education. My initial motivation for such study occurred from the identification of conceptions contrary to humanistic values between students from basic education. These conceptions are maintained and defended through arguments considered scientific by these subjects, that when asked about themes related to race, ethnicity, sexuality and social organization, manifested prejudices using elements of the biological speech, as a way to justify their ideas. With the propose to establish relations between Biological Speech and Human Rights Education, I appeal to the values present in the Universal Declaration of Human Rights that integrate a global project of teaching the prerogatives established by the United Nations Organization and to the analysis of three reference books from Modern Biology The Descent of Man and Selection in Relation to Sex, from Charles Darwin (1809 1882); The Selfish Gene, from Richard Dawkins (1941 -) and The Origin of Humankind, from Richard Leaky (1944-). The selected empiric material was organized and investigated with use of methodological principles of analysis of content, including the construction of the textual body that receives inferences in its development, supplying the visualization of speeches that refuse or corroborate values close to the humanistic conceptions present in the Human Rights. The diversity of the biological speeches analysed - occurring from different reasons, indicate the necessity of the teaching of altruistic and cooperative values, either for bringing revealing arguments of our selfish nature or being that they defend our tendency to the inborn altruism that need to be maintained and renforced by the cultural means. The themes developed in the work promote multiple discussions that can be used by educators in biological sciences so that, while teaching biology, divulge, educate and reflect about Human Rights.